A Comparative Study of Compact Multiband Bio-Inspired Asymmetric Microstrip Fed Antennas (BioAs-MPAs) for Wireless Applications - Jeremiah O. Abolade; Dominic B. O. Konditi; Vasant M. Dharmadhikary (Journal of Engineering)
A comparative analysis of compact multiband bio-inspired Asymmetric microstrip fed antennas (BioAs-MPAs) is presented in this paper for the first time. The proposed antennas are based on semi-Carica papaya-leaf shaped, semi-Monstera deliciosa-leaf shaped, semi-Vitis vinifera shaped, Defected Ground Structure (DGS) and L-slit techniques. The antennas are built on a 33 × 15 mm2 Rogers duroid 5880 substrate. The modelling equations for resonant frequencies of the proposed arbitrarily shaped radiating patch is based on modified circular patch modelling equations. The semi-Carica papaya-leaf antenna operates at 2.4 GHz and 4.4 GHz, Monstera deliciosa-leaf antenna operates at 2.6 GHz, 4.4 GHz and 5.5 GHz, while Vine-leaf antenna operates at 2.5 GHz and 5.4 GHz. The proposed BioAs-MPAs antennas radiation patterns at E-plane are Bi-directional in all the operating frequencies with suitable X-Pol purity and have Omnidirectional radiation patterns at H-Plane in all the operating frequencies. As a result of the analysis, it was found that each of the bio-inspired structures has its unique merit over the others. Owing to the small size, stable radiation pattern, acceptable gain and high radiation efficiency, the proposed BioAs-MPAs antennas are suitable for ISM band, Bluetooth, Wi-Fi, WiMAX, LTE, UMTS, Sub6 GHz 5 G band, ZigBee and RF-Altimeter used in unmanned aerial vehicle and Aviation industry.